2021
DOI: 10.24114/jipk.v3i2.28108
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-Modul Terintegrasi Media Berbasis Adobe Flash CS6 Untuk Meningkatkan Kemampuan Pemecahan Masalah Kimia Mahasiswa

Abstract: Supporting the implementation of an effective learning process cannot be separated from the use of teaching materials. Improving the quality of the learning process in higher education can be done with various strategies and one alternative that can be taken is the development of teaching materials. This study aims to develop an integrated e-module based on Adobe Flash CS6 media to improve students' chemistry problem solving skills on thermochemical material. The development model used refers to the ADDIE deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…Fakta menunjukkan bahwa dalam proses pembelajaran khususnya pembelajaran kimia, peserta didik cenderung lebih menghafal konsep, teori, dan prinsip tanpa memaknai proses perolehannya. Akibatnya, peserta didik menjadi kurang terlatih untuk berpikir dan menggunakan daya nalarnya dalam memahami fenomena alam yang terjadi ataupun ketika menghadapi masalah (Panggabean & Purba, 2021).…”
Section: Pendahuluanunclassified
“…Fakta menunjukkan bahwa dalam proses pembelajaran khususnya pembelajaran kimia, peserta didik cenderung lebih menghafal konsep, teori, dan prinsip tanpa memaknai proses perolehannya. Akibatnya, peserta didik menjadi kurang terlatih untuk berpikir dan menggunakan daya nalarnya dalam memahami fenomena alam yang terjadi ataupun ketika menghadapi masalah (Panggabean & Purba, 2021).…”
Section: Pendahuluanunclassified
“…This digital media can be in the form of websites, social media, digital images and videos, digital audio and others (Abdulrahaman et al, 2020;Basar et al, 2021;Indariani et al, 2018). Various studies have shown that interactive digital teaching modules are valid and feasible to use in the learning process with an outstanding category that can improve learning outcomes and problem solving skills (Aisyah et al, 2021;Herawati & Muhtadi, 2018;Panggabean & Purba, 2021). So based on the description above, this research is essential for the purpose develop interactive digital teaching modules based on DI (Different Instruction) on chemistry problem-solving abilities as a form of independent learning.…”
Section: Introductionmentioning
confidence: 99%
“…Students can read by feeling like reading a book physically because there is an animation effect where when switching pages it will look like physically opening a book. The final result can be saved to html, exe, zip, screen saver and app formats [16].…”
Section: Introductionmentioning
confidence: 99%